Efficacy of percutaneous and transcutaneous posterior tibial nerve stimulation on idiopathic overactive bladder and interstitial cystitis/painful bladder syndrome: A systematic review and meta‐analysis. Issue 2 (15th January 2022) - Ghavidel‐Sardsahra, Amirhossein; Ghojazadeh, Morteza; Rahnama'I, Mohammad Sajjad; Naseri, Amirreza; Yazdandoost, Shahabodin; Khezerloo, Taha; Seyedi‐Sahebari, Sepideh; Hosseinifard, Hossein; Vahed, Nafiseh; Mostafaei, Hadi; Salehi‐Pourmehr, Hanieh; Hajebrahimi, Sakineh
Abstract: Objectives: Percutaneous and transcutaneous posterior tibial nerve stimulation (PTNS and TTNS) showed a promising effect on overactive bladder (OAB) and interstitial cystitis/painful bladder syndrome. We aimed to give a systematic review and meta‐analysis on the efficacy and safety of these therapeutic methods as well. Methods: We searched studies available on PubMed, Embase, Cochrane, Scopus, Web of Science, and ProQuest on March 31, 2021, to find both published and unpublished studies. The retrieved articles were screened by two independent researchers and then the selected studies were critically appraised by Cochrane risk‐of‐bias tool for randomized trials, and Joanna Briggs Institute's checklist for quasi‐experimental studies. Finally, the results of studies were synthesized using Review Manager (RevMan) 5.4 statistical software when the data were homogenous. The meta‐analysis was performed by calculating the effect size (mean difference) and their 95% confidence intervals (CIs). Results: Of the total 3194 publications, 68 studies were included in our qualitative evaluation and 9 studies (11 trials) in the quantitative stage. When TTNS or PTNS were compared to sham, placebo, no treatment, or conservative management, a decrease in frequency of urination was observed in both TTNS (mean difference [MD]: −3.18, 95% CI: −4.42 to −1.94, and p  < 0.00001), and PTNS (MD: −2.84, 95% CI: −4.22 to −1.45, and p  < 0.00001), and overall TTNS or PTNS (MD: −2.95, 95% CI: −4.01 to −1.88, and p  < 0.00001). Significant improvements in mean voiding volume (MVV) and decreasing nocturia were also observed. Conclusions: Nerve stimulations either PTNS or TTNS appear to be effective interventions in treating refractory idiopathic OAB in terms of daily voiding frequency, MVV, urgency episodes, and nighttime voiding frequency. However, our result did not show any improvement in terms of urinary incontinence, postvoid residual volume or urge incontinence, and maximum cystometric capacity which emphasized the efficacy of these modalities on dry‐OAB rather than wet‐OAB.